Bird of Paradise Island, Tobago, B.W.I. - Allmon, Chas (Guardian Printery, 2011)
The postcard shows the Bird of Paradise Island, Tobago.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Islands--Trinidad and Tobago; Coasts--Trinidad and Tobago; Bird of Paradise Island; Birds--Conservation--Trinidad and Tobago; Bird refuges--Trinidad and Tobago